The Diversity and Dominance of Weeds in Various Population Proportions of Intercropping Soybeans With Corn - Agus Nugroho Setiawan; Sarjiyah Sarjiyah; Nur Rahmi (Politeknik Negeri Lampung., 2022)
Soybean is an important food crop for Indonesia after rice and corn. Soybean productivity in Indonesia is still low because most farmers use monoculture cropping patterns which has many weaknesses. Intercropping is an alternative to increase soybean productivity because it has many advantages. Soybeans can be intercropped with corn because the two plants have different physical characteristics, physiology and growth patterns. This research aimed to obtain information about the diversity and abundance of weeds in soybean and corn intercropping. The study was conducted using a single factor treatment design which will be arranged in a single plot field design, using Grobogan variety soybean and Bisma variety corn. The treatment was the proportion of soybean and corn populations which consisted of 4 proportions, i.e. 2:1, 3:1, 4:1, and 5:1, and monoculture soybeans were also planted as a control. Observations on weeds were carried out at the age of 2, 8, and 12 weeks after planting (before harvest) with vegetation analysis. The size of each sample is 0.5 m x 0.5 m with 15 sample plots/plots. The results showed that based on the summed dominance ratio (SDR) in the research area, 16 species of weeds were dominated by broadleaf weeds, with the dominant types of weeds being Phyllanthus urinaria L., Eleusine indica L., and Oryza sativa L. The results showed that based on the Summed Dominance Ratio (SDR) in soybean there were 16 species of weeds that were dominated by broadleaf weeds, with the dominant types of weeds being Phyllanthus urinaria L., Eleusine indica L., and Oryza. sativa L. Weeds growing on soybean intercropping with corn and soybean monoculture have a medium diversity index (H').